Management Strategy for Pacu Jalur Event as a Cultural Tourism Attraction in Kuantan Singingi Regency, Riau Province - Ananda, Annisa Rizki; Kristianto, Yohanes; Indrawati, Yayu (Cita Konsultindo Research Center, 2024)
Event management is a vital domain within the management of tourism destinations. This study employs a qualitative approach with a descriptive methodology, aiming to delve into and portray phenomena, events, and situations in a thorough and comprehensive narrative manner. Data were collected through triangulation to ensure validity and reliability. In-depth interviews were conducted with informants including the Tourism Office of Kuantan Singingi Regency, academics, local communities, private sector representatives, and media. Observations were carried out via quasi-participation, where the researcher partially engaged in observing the Pacu Jalur event. Documentation related to the Pacu Jalur festival was also gathered as evidence for this study. Additionally, a literature review of other research was conducted to enhance both theoretical and practical insights. The findings reveal that Pacu Jalur, as a tourist attraction, holds significant tourism potential. However, the tourism product components for visitors remain minimal. The stages of event management are neither effective nor efficient. The promotional mix by the Tourism and Culture Office of Kuantan Singingi Regency is social media-based but has yet to reach a broad tourism market. Strategies identified include the political aspect indicating strong government support but also political instability, which could hinder tourism operators. The economic aspect shows that while the Pacu Jalur event generates substantial revenue from hotels, restaurants, and parking, it lacks official sponsors. The social aspect demonstrates that the community is actively involved in both the event's execution and the preservation of this tradition. The environmental aspect reveals that Pacu Jalur has adopted selective logging practices to maintain environmental sustainability. The legal aspect indicates that regulations concerning Pacu Jalur have been formalized as guidelines under regent regulation No. 16 of 2023. In conclusion, event management and promotional strategies are not yet functioning effectively and efficiently, necessitating the implementation of strategies to achieve optimal results.